2019
DOI: 10.1111/opo.12601
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of detection of patients with narrow angles by community optometrists in Scotland

Abstract: Aim: To examine the accuracy of referrals by community optometrists for suspected primary angle closure, including primary angle closure suspects, primary angle closure and primary angle closure glaucoma. Methods: A retrospective review of 769 consecutive patients referred by community optometrists to the glaucoma clinic at a university hospital in Scotland. Ninety-five of 715 eligible subjects (13%) were referred due to suspected angle closure. All subjects had a comprehensive eye examination in the glaucoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In a retrospective study, Sii et al 35 observed a significant decline in the first visit discharge rate when comparing two 2-month periods both before (29.2% first visit discharge rate) and after (19.2% first visit discharge rate ) the publication of SIGN 144, while also observing room for improved adherence to referral criteria. On a more specific clinical query, Annoh et al 36 recently examined the accuracy of referrals for primary angle closure related diagnoses in Scotland. In 769 consecutive referrals they determined that community optometrists had 'good' ability to detect eyes at risk of angle closure, with only 12% of those referred for possible angle closure being discharged at the first visit.…”
Section: Effectiveness Of Traditional Case Finding and Grfsmentioning
confidence: 99%
“…In a retrospective study, Sii et al 35 observed a significant decline in the first visit discharge rate when comparing two 2-month periods both before (29.2% first visit discharge rate) and after (19.2% first visit discharge rate ) the publication of SIGN 144, while also observing room for improved adherence to referral criteria. On a more specific clinical query, Annoh et al 36 recently examined the accuracy of referrals for primary angle closure related diagnoses in Scotland. In 769 consecutive referrals they determined that community optometrists had 'good' ability to detect eyes at risk of angle closure, with only 12% of those referred for possible angle closure being discharged at the first visit.…”
Section: Effectiveness Of Traditional Case Finding and Grfsmentioning
confidence: 99%
“…In addition, given the needed training in an optometry setting, such assessment can reduce the number of referrals for double screening, which takes on patient time, and which may also lead to disease progression. is will also provide a form of standardization for the rising concern about optometrists using gonioscopy in the primary care setting for glaucoma detection and the need for training nonophthalmic personnel in screening techniques, which can increase the sensitivity and specificity to a level of accurate positive prediction (62%) [45][46][47][48].…”
Section: Possible Applications In Ophthalmologymentioning
confidence: 99%
“…A number of peer‐reviewed studies have evaluated aspects of the new Scottish GOS contract including the quality of referrals, access to and distribution of services, the use of clinical equipment and practitioner preferences relating to the management of ocular conditions. One particular area that has attracted the attention of researchers is the impact of the new GOS contract on the quality of glaucoma referrals . Comparing the quality of more than 300 glaucoma referrals before and after the new GOS, Ang et al .…”
Section: Comparison Between Eye‐care Models and Supporting Evidencementioning
confidence: 99%
“…A recent retrospective case review investigated the accuracy of referrals for suspected primary angle closure over a 6‐month period in 2016 (10 years after the introduction of the new GOS) and indicated that optometrists possess a good ability to diagnose narrow angles correctly …”
Section: Comparison Between Eye‐care Models and Supporting Evidencementioning
confidence: 99%
See 1 more Smart Citation